KESEIMBANGAN TINGKAT PELAYANAN PAJAK DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - -, Yulianto (www.bsi.ac.id, 2009)
Abstract:Enactment of Law No. 22 of 1999 changed to Act No. 32 of 2004 and Act No. 25 of 1999 was changed to Law Number 33 Year 2004 brings new implications for the development of gover nance systems in the region. Impact most felt by the local government is given such broad authority. This is what is defined as the granting of autonomy to regional real and responsible. In essence, the granting of autonomy given the consideration that daerahlah knows better growing conditions in the region. However, the implications of decentralization is that regional autonomy demands in various fields. Financial balance system between the Central and Local Government hopes to make the PAD as a major source of funding is still difficult to do. The fact that there are areas that have capacity, especially in terms of government funding and local development district has a proportion of revenue to total local revenue is still below15percent.Keyword:Central government financial balance & Regional, Local Taxes, Government and regional development.